2013
DOI: 10.1002/dc.22990
|View full text |Cite
|
Sign up to set email alerts
|

The impact of LSIL‐H terminology on patient follow‐up patterns

Abstract: The Papanicolaou (Pap) test category of "low grade squamous intraepithelial lesion, cannot exclude high grade squamous intraepithelial lesion" (LSIL-H) is not recognized by The Bethesda System but is commonly used. It is essentially an amalgamation of the official LSIL and ASC-H categories. Since these two categories have similar follow-up algorithms, the clinical utility of the combined LSIL-H category is unclear. We have therefore studied follow-up patterns for these three entities in our laboratory to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Previous papers cite that the histologic follow-up rate of high-grade lesions is intermediate between LSIL and HSIL and that fewer are associated with high-risk HPV types. [15][16][17][18] In some studies, 20 ASC-H and LSIL-H appear to have similar rates of high-grade lesions on follow-up, but others show LSIL-H to be followed by more high-grade lesions 15 or more often associated with high-risk HPV than ASC-H. 18 Thrall et al 20 also comment that the rate of initial biopsy follow-up for women with LSIL-H is similar to that for ASC-H, but that women with LSIL-H and initial negative biopsy are more likely to undergo a second biopsy than women with ASC-H. Many laboratories either are unaware of the TBS 2014 final recommendations or choose to use LSIL-H, perhaps because of pathologist preference or concerns that patients may not receive sufficient follow-up by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers cite that the histologic follow-up rate of high-grade lesions is intermediate between LSIL and HSIL and that fewer are associated with high-risk HPV types. [15][16][17][18] In some studies, 20 ASC-H and LSIL-H appear to have similar rates of high-grade lesions on follow-up, but others show LSIL-H to be followed by more high-grade lesions 15 or more often associated with high-risk HPV than ASC-H. 18 Thrall et al 20 also comment that the rate of initial biopsy follow-up for women with LSIL-H is similar to that for ASC-H, but that women with LSIL-H and initial negative biopsy are more likely to undergo a second biopsy than women with ASC-H. Many laboratories either are unaware of the TBS 2014 final recommendations or choose to use LSIL-H, perhaps because of pathologist preference or concerns that patients may not receive sufficient follow-up by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The current third edition of the Bethesda system places bizarre cells, as we described them above, implicitly into the LSIL category . There are some authors who are in favour of use of the LSIL‐H category; however, such suggestions have not reached a consensus yet . We suppose it is conceivable that, from a practical point of view, the term LSIL‐H could be used with a certain degree of convenience in cases of BCD when no HSIL cells are found in a smear.…”
Section: Discussionmentioning
confidence: 97%
“…Several reported studies have indicated that patients with LROH/LSIL‐H appeared to have an intermediate risk of harbouring or developing high‐grade squamous lesions on biopsy and a different HPV prevalence compared with LSIL and ASC‐H, ranging from 22.8% to 59% of cases . Because of the increased incidence of high‐grade lesions found on histology, comparable to patients with HSIL, it has been proposed that these patients may require a clinical management similar to HSIL diagnosis …”
Section: Introductionmentioning
confidence: 99%